2000
DOI: 10.1007/s11920-000-0051-1
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar disorder in youth

Abstract: The debate regarding the possible existence of prepubertal bipolar illness has surfaced at various points in history. In its most recent incarnation, proponents of a childhood bipolar diagnosis argue that there is an early-onset form of bipolar illness that is highly comorbid and characterized by simultaneous irritability and depression. Others have suggested that childhood manic symptoms are more likely a nonspecific indicator of risk, or may be the result of symptom overlap with various other forms of childh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 76 publications
0
10
0
1
Order By: Relevance
“…Although a DSM-III-R diagnosis of mania has been reported in about 16% of outpatient users 12 years of age or younger,12 these data suggest that manic symptoms (as opposed to a DSM-IV diagnosis of bipolar disorder) may be even more common in young outpatient utilizers. Participating children who scored positive for symptoms of mania display very different behavior than children who scored negative, as noted in a number of previous studies examining symptoms in bipolar youth compared to youth with other diagnoses 11, 33, 48…”
Section: Discussionmentioning
confidence: 68%
“…Although a DSM-III-R diagnosis of mania has been reported in about 16% of outpatient users 12 years of age or younger,12 these data suggest that manic symptoms (as opposed to a DSM-IV diagnosis of bipolar disorder) may be even more common in young outpatient utilizers. Participating children who scored positive for symptoms of mania display very different behavior than children who scored negative, as noted in a number of previous studies examining symptoms in bipolar youth compared to youth with other diagnoses 11, 33, 48…”
Section: Discussionmentioning
confidence: 68%
“…For example, caregiver reports indicate there are executive functioning deficits in adolescents with bipolar disorder (DelBello et al, 2004) and a longitudinal study of young adults with bipolar disorder has reported attentional deficits throughout adolescence (Carlson and Meyer, 2000). A recent study by Goldstein et al (2006) reported deficits in social behavior and interpersonal functioning in adolescents with bipolar disorder, even when relatively well.…”
Section: Neuropsychological Profile Of Juvenile Bipolar Disorder Compmentioning
confidence: 99%
“…B ipolar disorder has been observed in adolescents (Carlson and Strober, 1978;Lewinsohn et al, 1995) and prepubertal school-age children (Carlson 1998;Carlson and Meyer 2000;Geller et al 1994Geller et al , 1998Weller et al 1986b;Wozniak et al 1995). It is of interest to determine if the illness occurs in preschool children.…”
Section: Introductionmentioning
confidence: 99%